The Long-Term Impact of the Earned Income Tax Credit on Children’s Education and Employment Outcomes - Bastian, Jacob; Michelmore, Katherine (Journal of Labor Economics, 2018)
Using 4 decades of variation in the federal and state Earned Income Tax Credit (EITC), we estimate the impact of exposure to EITC expansions in childhood on education and employment outcomes in adulthood. Reduced-form results suggest that an additional $1,000 in EITC exposure when a child is 13–18 years old increases the likelihood of completing high school (1.3%), completing college (4.2%), and being employed as a young adult (1.0%) and earnings by 2.2%. Our analysis reveals that the primary channel through which the EITC improves these outcomes is increases in pretax family earnings.